Relationship of Puddles, Swamps, Bushes, Cattle Cages to Malaria Incidence in Endemis District, North Labuhan Batu Regency in 2022 - Shinta Andria Chairani; Nurmaini Nurmaini; Rahayu Lubis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is relationship of puddles, swamps, bushes, cattle cages to malaria incidence in Endemis District, North Labuhan Batu Regency in 2022. This type of research is an analytical survey research with a case control research design. The population in this study are all residents in Kualuh Leidong Sub-District and Kualuh Hilir who suffered from malaria based on the results of the blood preparation examination, which was indicated by the discovery of plasmodium in the blood by laboratory personnel and was declared positive for malaria. The sample in this study is 114 consisting of 57 cases and 57 controls who have the same characteristics (age and sex). Data analysis in this study using bivariate analysis. The results show that there is a significant relationship between puddles and malaria incidence in Endemis District, North Labuhan Batu Regency in 2022. There is a significant relationship between swamps and malaria incidence in Endemis District, North Labuhan Batu Regency in 2022. There is a significant relationship between bushes and malaria incidence in Endemis District, North Labuhan Batu Regency in 2022. There is no significant relationship between cattle cages and malaria incidence in Endemis District, North Labuhan Batu Regency in 2022.